Mobilisation and dynamics of energy reserves in different tissues of Donax trunculus (Bivalvia: Donacidae) in the Gulf of Tunis (eastern Mediterranean Sea, Tunisia). Issue 1 (2nd January 2021) - Boussoufa, D; Chalouati, H; Ghazali, N; Navarro, JC; El Cafsi, M
Abstract : Seasonal changes in condition index and the biochemical components (proteins, lipids and glycogen) of the gonad/digestive gland, foot, labial palp, mantle, gills and adductor muscles of Donax trunculus Linnaeus, 1758 from the Gulf of Tunis were monitored seasonally, from November 2006 to October 2007, in relation to environmental conditions and reproductive events. The condition index increased during late gametogenesis and the ripe stage, coinciding with enrichment of the water by phytoplankton, and decreased during late summer and autumn (i.e. the spawning and rest periods). Glycogen increased during early gametogenesis and peaked during winter, pointing to its mobilisation in the formation of active ripe gametes. The foot, gonad/digestive gland, and adductor muscle were the three major glycogen-reserve tissues. Protein content was high during the end of summer in the whole individual and during autumn in the gonad/digestive gland. Lipid content started to increase as gametogenesis began, reached its peak at gonad ripeness and during the early spawning stage (summer) and sharply declined due to the shedding of gametes (autumn). A transformation of glycogen for de novo synthesis of lipids, in the gonad/ digestive gland, was suggested during the later stages of the gonadic cycle, in support of gametogenesis. Temporal fluctuations in environmental factors, particularly temperature and food supply, drive the cycle of storage and utilisation of metabolic energy reserves which in turn govern gametogenesis in Donax trunculus .